PENGARUH LINGKUNGAN KERJA DAN FASILITAS KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA BPJS KETENAGAKERJAAN CABANG PEKANBARU PANAM - Alfi Yushro; Arman Arman; Adi Setiawan (STIE Bangkinang Publishing, 2022)
This study was conducted with the aim of testing the effect of work environment and work facilities on employee job satisfaction at BPJS Ketenagakerjaan Pekanbaru Panam Branch and the variables that affect employee job satisfaction at BPJS Ketenagakerjaan Pekanbaru Panam Branch. The population in this study were all employees of the BPJS Ketenagakerjaan branch office of Panam Pekanbaru as many as 30 people where 26 people had a bachelor's degree (S1) education and 4 people from high school equivalent. The sampling technique was carried out using a saturated sampling technique, which means that if there are less than 100 people, it is better to take all of them. This is often done when the population is relatively small. The sample set in this study were all employees of the Bpjs Manpower at the Panam Pekanbaru branch office as many as 30 people. Hypothesis testing using multiple linear regression analysis with the help of SPSS 23.00 for windows. The results showed that simultaneously and partially the work environment and work facilities on employee job satisfaction at BPJS Ketenagakerjaan Pekanbaru Panam Branch. Partially.